2005
DOI: 10.1007/s10692-006-0005-4
|View full text |Cite
|
Sign up to set email alerts
|

Modified Fibre and Film Materials

Abstract: Some results of studies on modification of polymers and polymeric materials conducted in the Department of Chemical Fibre Technology at Moscow State Textile University are examined. The promise of using the developed methods for creating materials for special applications is demonstrated: fire-retardant, chemisorption, antiadhesive, for medicine.Chemical modification is one of the most efficient methods of deliberately altering the structure, composition, and properties of fibre and film materials. Investigati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…In this work, we further extended this theory to the fabrication of acid-resistant fabric. Galbraikh [15] and several other authors have demonstrated that fluorochemicals could effectively provide resistant properties to corrosive solution and enable an acid-proof coating on fabric. However, the acid-proof permeability (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we further extended this theory to the fabrication of acid-resistant fabric. Galbraikh [15] and several other authors have demonstrated that fluorochemicals could effectively provide resistant properties to corrosive solution and enable an acid-proof coating on fabric. However, the acid-proof permeability (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Corrosive acid solutions are primarily composed of a water-based phase, and consequently, many researchers have applied the hydrophobic mechanism to the acid-proof theory. In the case of acidic solutions, Gal’braikh and coworkers (2005) have demonstrated that low surface energy molecules such as fluorochemicals could effectively offer resistant properties to the corrosive solution while simultaneously repelling water due to the hydrophobicity of specially treated fluorochemicals. However, the standard requirements for protective attire for those who work with acids on a day-to-day basis still cannot be reached if the textile was treated with fluorochemicals only (according to Chinese National Standard GB 24540-2009, Protective clothing—Protective clothing against liquid acid and alkalis).…”
mentioning
confidence: 99%